Aplicación móvil con realidad aumentada para impulsar el desarrollo cognitivo y motriz, en niños de 2 a 3 años de edad. - Aimacaña Morocho, Kleber Fernando (2020)
The mobile application that was developed had as main objective to promote cognitive and motive development in children from two to three years old using augmented reality technology, through the use of programming tools for mobile devices such as Unity, Vuforia and Blender; In the same way the evolutionary development prototype model was used, which helped to interact with the requesting user who contributed to the App's development which is called “JADE”, that has 2 sections which are: cognitive development and motive development; 3 modules are included in the cognitive development: fruit, animals and professions, at these modules you must use unique images designed by the developers, which are found on the App's website, on the other hand the motive development section is divided into 2 modules that contain farm animals and fruit; To interact with this section the user must download the images from the App's web page. The developed web page is implemented in the following link: http://jadelatacunga.site, where the App installer will be available and the gallery is divided in animals, fruit and professions. The application was validated on Child Development Center (CDI) called "Gotitas de Amor San Felipe" located at Eloy Alfaro parish that belongs to Economic Ministry and Social Inclusion (MIES), where was obtained as a result that more than 50% of children manage the application, which serves as support for their cognitive and motive development, which is why the fulfillment of the objectives set at the beginning of the project could be determined.